A force-resisting rotary friction damper (RFD): Verification and comparison with traditional RFD. (15th December 2022) - Li, Dingbin; Zhou, Yun
Highlights: A novel force-resisting rotary friction damper (RFD) was proposed. The proposed RFD has a larger friction moment than traditional RFD under the same preload. The proposed RFD has a smaller pressure on friction shim and stress on steel plates than traditional RFD under the same preload. The concept of the force-resisting RFD was verified by a test and numerical analysis. Abstract: A force-resisting rotary friction damper (RFD) is proposed in this paper, which can be applied where there is a large rotational deformation. Its exclusive configuration lies in that multiple bolts are symmetrically arranged on concentric circles centered on the hinge pin to apply preload, resulting in: [i] an independent force-transfer capability decoupled with the moment to meet shear or axial forces-transfer demands and [ii] providing larger friction bending-moment with smaller compressive stresses on friction shim and lower maximum stress on the steel plate compared to the traditional RFD under the same preload and friction coefficient. A prototype of the proposed RFD was manufactured and tested twice without tightening the bolts again and replacing the friction shims by cyclic loading to investigate its mechanical property and recoverability. The test results showed that the moment–angle hysteretic curve of the proposed RFD was an ideal rectangle, indicating a reasonable mechanism. The variation of the friction bending-moment was within 4.00 % between the two-time tests, indicating that the proposed RFD has satisfactory recoverability and can uninterruptedly provide energy absorption during dense aftershocks. Then, a refined finite element model was established and calibrated by the test results. For the numerical prototype studied, the friction bending-moment of the proposed RFD was approximately 35 % larger than that of the traditional RFD while its maximum pressure on friction shim was about 40 % of the corresponding traditional RFD. The difference in the friction moment between the theoretical and numerical results was within 4.50 %. The concept of the force-resisting RFD was justified.